Pricing Policies and Inflation Inertia - Kumhof, Michael (IMF Working Papers; Working Paper ;, 2003)
This paper provides a monetary model with nominal rigidities that differs from the conventional New Keynesian model with firms setting pricing policies instead of price levels. In response to permanent or highly persistent monetary policy shocks this model generates the empirically observed slow (inertial) and prolonged (persistent) reaction of the inflation rate, and also the recession that typically accompanies moderate disinflations. The reason is that firms respond to such shocks mostly through a change in the long-run or inflation updating component of their pricing policies. With staggered pricing policies there is a time lag before this is reflected in aggregate inflation.